The Influence of Financial Literacy, Income, and Spending Control on Household Financial Management among Housewives in Rural Indonesia - Muh Fahrurrozi; Susilawati Susilawati; Iswari Komalasari (JMET: Journal of Management Entrepreneurship and Tourism, 2026)
This study aims to analyze the influence of financial literacy, income, and expenditure control on household financial management among housewives in Tangar Hamlet, Setungkep Lingsar Village. This research employs a quantitative approach with an associative design. The sample consisted of 152 housewives selected through simple random sampling from a population of 244 individuals. Data were collected using a Likert-scale questionnaire and analyzed using classical assumption tests and multiple linear regression with the assistance of SPSS. The findings reveal that income has a positive and significant effect on household financial management, indicated by a t-value of 4.274 > 1.976 and a significance value of 0.000 < 0.05. Meanwhile, financial literacy does not have a significant effect, as shown by a t-value of 1.360 < 1.976 and a significance value of 0.176 > 0.05. Similarly, expenditure control does not significantly influence financial management, with a t-value of 1.646 < 1.976 and a significance value of 0.102 > 0.05. However, simultaneously, financial literacy, income, and expenditure control significantly affect household financial management, as indicated by an F-value of 18.589 > 2.67 and a significance value of 0.000 < 0.05. These findings confirm that income is the dominant factor determining the effectiveness of household financial management, while financial literacy and expenditure control need to be strengthened to contribute more substantially to household financial management practices among housewives.